On the Relationship between Mathematical Theories and Financial Markets A Critical Review on the Book Lecturing Birds on Flying - Hojjatollah Sadeqi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The financial crisis of 2007-2008 has been the subject of research in different ways. The role of quantitative models and mathematical theories in the occurrence of this crisis and the other complications that such models cause in financial markets is the main theme of the book Lecturing Birds on Flying. By explaining the role of the educational system in creating a gap between theory and practice and the role of Quants in promoting and applying quantitative and computational models, the author gives a different account of the causes of financial crises. In this article, while examining the form and content of this work, by analyzing the theme as well as textual analysis techniques, the most important themes of this work as well as its foundations and place in the texts of financial knowledge are reviewed. Criticism of models such as value at risk, option pricing model, and copula functions has shown their contribution to bankruptcies and crises and has suggested that reform of the management and economics education system would make the financial models more realistic.